2004
DOI: 10.1117/12.524865
|View full text |Cite
|
Sign up to set email alerts
|

Perception and detection of counterfeit currency in Canada: note quality, training, and security features

Abstract: Commissioned by the Bank of Canada to help improve the detection of counterfeit currency, we designed a series of tests of performance to explore the contributions of note quality, sensory modality, training, security features and demographic variables to the accuracy of counterfeit detection with three different note types. In each test, participants (general public, and cash handlers, divided amongst commercial cash handlers and bank tellers) were presented with notes, one at a time, for up to seven seconds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 3 publications
3
21
0
Order By: Relevance
“…However, we are not aware of any research that provides evidence in support of the assumption that more counterfeits are detected when the quality of banknotes in circulation is high. To our knowledge, the only study touching on this issue was performed by the Dalhousie University and commissioned by the Bank of Canada (Klein et al, 2004). In this research, no evidence is found that quality of circulation has an impact on the detection rate of counterfeits, while the performance of detecting low quality genuine notes proves less accurate in a high quality notes context (more false alarms).…”
Section: Introductionmentioning
confidence: 49%
See 2 more Smart Citations
“…However, we are not aware of any research that provides evidence in support of the assumption that more counterfeits are detected when the quality of banknotes in circulation is high. To our knowledge, the only study touching on this issue was performed by the Dalhousie University and commissioned by the Bank of Canada (Klein et al, 2004). In this research, no evidence is found that quality of circulation has an impact on the detection rate of counterfeits, while the performance of detecting low quality genuine notes proves less accurate in a high quality notes context (more false alarms).…”
Section: Introductionmentioning
confidence: 49%
“…The results of Jonker et al (2006) show that, overall, the Dutch public is quite capable of recognising a counterfeit note: without having practised or received any feedback, members of the general public correctly identify 83% of the counterfeit notes they have been given to examine. Klein et al (2004) find that Canadian consumers detect 69% of counterfeits they examine in a test. Detection rates of genuine banknotes are also very high.…”
Section: Research Questions and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They use test sets with three stacks, each consisting of 72 banknotes, and find that consumers (cashiers) are able to increase their detection rates from 83% (96%) in the first stack to 93% (99%) in the third stack. 13 Klein et al (2004) also find significant learning effects in a banknote detection test in Canada. Unfortunately, they do not distinguish between hits and false alarms.…”
Section: Figure 8: Predicted Detection Rates and Their 95% Confidencementioning
confidence: 83%
“…The results of Jonker et al (2006) show that, overall, the Dutch public is quite capable of recognising a counterfeit note: without having practised or received any feedback, members of the general public correctly identify 83% of the counterfeit notes they have been given to examine. Klein et al (2004) find that Canadian consumers detect 69% of counterfeits they examine in a test. 3 Detection rates of genuine banknotes are also very high.…”
Section: Research Questions and Literature Reviewmentioning
confidence: 95%